Analysis of a low-cost anthropomorphic sensory platform for the world first minibus test. Issue 2 (15th January 2019) - Stopforth, Riaan; Proctor-Parker, Craig; Davrajh, Shaniel
Abstract : Purpose: The purpose of this paper includes results of some of the tests involved for the design and implementation of low-cost crash anthropomorphics (ATPs) fitted with sensory systems to measure forces that would have been experienced by passengers in the vehicle, commonly used for public transport within South Africa. Design/methodology/approach: This paper presents the description of the implemented low cost ATPs and the analysis of the data obtained from the sensory system within the torso of the ATPs and in the head of a single ATP, to identify if a documented threshold is exceeded. The autopsy of the ATPs is performed to identify injuries. Findings: The recorded results showed the type of injuries that could have occurred when an accident has occurred with occupant in the minibus taxi. The autopsy performed on the ATPs showed feasible injuries that could be obtained by a person in a similar scenario. Research limitations/implications: The ATPs were to be designed and constructed with the sensory system, with a budget of ZAR13, 000/US$1, 000. Originality/value: The contributions of this paper are as follows: present the test results of two ATPs, and discuss them, for a loss of control of a minibus on a wet surface, which has been indicated as a world first test; And identify the need for a data fusion of sensory information to evaluate the injuries with the autopsy performed.